How defensive medicine is defined in European medical literature: a systematic review - Nathalie Baungaard; Elisabeth Assing Hvidt; Helle Gerbild; Merethe Kirstine Andersen; Jesper Lykkegaard; Pia Ladeby Skovvang (BMJ Open)
Objectives Defensive medicine has originally been defined as motivated by fear of malpractice litigation. However, the term is frequently used in Europe where most countries have a no-fault malpractice system. The objectives of this systematic review were to explore the definition of the term ‘defensive medicine’ in European original medical literature and to identify the motives stated therein.Design Systematic review.Data sources PubMed, Embase and Cochrane, 3 February 2020, with an updated search on 6 March 2021.Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, we reviewed all European original peer-reviewed studies fully or partially investigating ‘defensive medicine’.Results We identified a total of 50 studies. First, we divided these into two categories: the first category consisting of studies defining defensive medicine by using a narrow definition and the second category comprising studies in which defensive medicine was defined using a broad definition. In 23 of the studies(46%), defensive medicine was defined narrowly as: health professionals’ deviation from sound medical practice motivated by a wish to reduce exposure to malpractice litigation. In 27 studies (54%), a broad definition was applied adding … or other self-protective motives. These self-protective motives, different from fear of malpractice litigation, were grouped into four categories: fear of patient dissatisfaction, fear of overlooking a severe diagnosis, fear of negative publicity and unconscious defensive medicine. Studies applying the narrow and broad definitions of defensive medicine did not differ regarding publication year, country, medical specialty, research quality or number of citations.Conclusions In European research, the narrow definition of defensive medicine as exclusively motivated by fear of litigation is often broadened to include other self-protective motives. In order to compare results pertaining to defensive medicine across countries, future studies are recommended to specify whether they are using the narrow or broad definition of defensive medicine.PROSPERO registration number CRD42020167215.